Afiches y avisos publicitarios: estructura y organización - Mendocilla Zavaleta, Yesmin Dagner (2019)
The present work of professional sufficiency is structured in three parts, which have been carefully structured due to their importance and order, the thematic field worked is the poster and the advertising notice: structure and organization. In addition to two livelihoods, one pedagogical and another scientific._x000D_ In the presented learning session, the competence, capacities and performances to be treated for its development are specified, as well as the parties with their respective activities to be developed. In the pedagogical support, everything corresponding to a learning session is specified, defining concepts such as: society, learning, education, skills, abilities, strategies, evaluation, etc. In addition to the learning theories that will serve for its execution._x000D_ In what corresponds to the theoretical support, this is focused on defining the conceptual part of the poster and the advertisement, its structures and its organization, adding to each of these concepts, strategies and examples so that it is easy to understand and understand for Students with whom you are going to work.